The conclusion of the strong consistency of M-estimator of exchangeable random variable samples. Issue 4 (3rd July 2016) - Huang, Zhaoxia; Qian, Fucai; Liu, Jun
Abstract: In this paper, the strong consistency of M-estimator in the linear models for exchangeable random variable samples is studied. Some suitably sufficient conditions about the strong consistency of M-estimator are given by performing the strict theoretical analysis. The results are much better than the strong consistency of M-estimator in the linear models for the identically random variable samples.